2019
DOI: 10.1186/s12967-019-2011-3
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human study of TK-positive oncolytic vaccinia virus delivered by adipose stromal vascular fraction cells

Abstract: Background ACAM2000, a thymidine kinase (TK)-positive strain of vaccinia virus, is the current smallpox vaccine in the US. Preclinical testing demonstrated potent oncolytic activity of ACAM2000 against several tumor types. This Phase I clinical trial of ACAM2000 delivered by autologous adipose stromal vascular fraction (SVF) cells was conducted to determine the safety and feasibility of such a treatment in patients with advanced solid tumors or acute myeloid leukemia (AML). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…As complement inhibition seems to play a crucial role in virus depletion following intravenous application [22], a new strategy is the application of an anti-C5-antibody (eculizumab) prior to virotherapy [NCT02714374]. Another recent approach to prevent intravascular virus clearance is to administer virus loaded cells as a carrier system for viral particles [23,24]. Reasonable options for NENs constitute intravenous administrations as well as direct virus injections into the hepatic artery in case of liver involvement (NCT02749331, [9];).…”
Section: Introductionmentioning
confidence: 99%
“…As complement inhibition seems to play a crucial role in virus depletion following intravenous application [22], a new strategy is the application of an anti-C5-antibody (eculizumab) prior to virotherapy [NCT02714374]. Another recent approach to prevent intravascular virus clearance is to administer virus loaded cells as a carrier system for viral particles [23,24]. Reasonable options for NENs constitute intravenous administrations as well as direct virus injections into the hepatic artery in case of liver involvement (NCT02749331, [9];).…”
Section: Introductionmentioning
confidence: 99%
“…The dose range for ACAM2000 was between 1.4 × 10 6 and 1.8 × 10 7 PFU/mL, administered via intravenous, intra-tumoral and intra-peritoneal injections. This study demonstrated that ACAM2000 was very safe and in some patients led to a substantial tumor size reduction at six months post-treatment, or complete eradication of the solid tumor after three months to treatment [197].…”
Section: Poxviridaementioning
confidence: 70%
“…Besides this, the evaluation of the antitumor effect for the solid tumor can be conducted more effectively and conveniently by the changes of lesions. However, virotherapy has begun to show its signals of antitumor effect in acute myeloid leukemia (AML) 152 and myeloma 153,154 . Interestingly, favorable results were able to be observed in tumors with different expression of endothelial growth factor receptor (EGFR) or the level of retinoblastoma phosphorylation.…”
Section: Introductionmentioning
confidence: 99%